Pengaruh Job Insecurity, Job Satisfaction dan Lingkungan Kerja Terhadap Turnover Intention Karyawan - Novi Ali Marzuqi (Jurnal Ilmu Manajemen, 2021)
Turnover intention occurs when employees fail to get what they expect from their place of work, such as work satisfaction, comfort at the workplace, job future guarantee, etc. Employees who desire to resign from their company will start looking for job vacancies in other places that offer better opportunities than their current workplace. When they find a job vacancy that matches them, they will resign from their company. This research aimed to determine the impact of job insecurity, job satisfaction, and work environment on employee turnover intention. The research sample used was 80 outsourcing employees from PT Shelter Nusa Indah. The data analysis technique used in this study is the Multiple Linear Regression model using the IBM SPSS 23 program. The results of this study are that job insecurity has a positive and significant effect on turnover intention. Job satisfaction and work environment have a negative and significant impact on turnover intention. The managerial implications of this research are expected to be suggestions in making company policies related to turnover intention. The company is expected to reduce feelings of restlessness, anxiety and worry over the threats experienced by employees regarding their future in the company. The company is expected to give appreciation or reward to employees who have good performance and dedication to the company's progress. The company is expected to maintain and create a comfortable work environment for employees.